Absorption of CO2 with supported imidazolium‐based ionic liquid membranes. Issue 8 (15th December 2014) - Cao, Baichuan; Yan, Weiheng; Wang, Jin; Ding, Hong; Yu, Yang
Abstract BACKGROUND Ionic liquids (ILs) are considered to be one of the future solutions to CO2 emission control because of their high CO2 solubility. Infiltrating ionic liquids into porous materials to prepare a supported ionic liquid membrane (SILM), could increase the absorption efficiency. RESULTS Four SILMs were prepared from imidazolium‐based ILs and PVDF microporous membranes. The CO2 absorption capacities of the SILMs were in the range of 0.88–3.64 mol mol−1, which were much higher than the solubility in ILs. After 20 min desorption at 60 °C or 0.08 MPa negative pressure, desorption rate reached 90%. And under the combined condition of 60 °C and 0.08 MPa, the desorption period was shortened and full desorption was obtained. The renewed SILMs maintained excellent CO2 absorption performance during several absorption–desorption cycles. A new peak at 1274–1284 cm−1 on the surface enhanced Raman scattering (SERS) spectra indicated the absorbed CO2, and some shifts of typical ILs vibration bands showed some probable structures related to CO2 absorption. CONCLUSION SILMs improved the mass transfer process and resulted in excellent CO2 absorption capacity. SILMs performed well in multiple absorption–desorption cycles, and showed great potential for industrial application. SERS is a feasible method for the characterization of SILMs. © 2014 Society of Chemical Industry